The Relationship Between ESG Disclosure and Corporate Financial Performance (CFP): Evidence from FTSE350. - Zhu, Wenting (2020)
In recent years, companies worldwide have transformed their short-term goals into profit maximization to achieve long-term sustainable environmental, social, and governance (ESG). Stakeholders have gradually realized that ESG has become an essential source of enterprise risk, which may influence the enterprises financial performance and profitability of the company. This research aims to understand the relationship between ESG disclosure and corporate financial performance (CFP). Many studies have shown that ESG could increase the financial performance of companies. However, the impact of ESG disclosure, E disclosure, S disclosure, and G disclosure on financial performance has not been further explored. As people pay more attention to ESG information, ESG information is also important to investors, which requires better disclosure practice. This study will investigate the relationship between ESG disclosure and CFP. This dissertation takes the UK FTSE350 from 2016-2018 as a sample to explore the relationship between the two. Two various test methods, OLS and GLS, are used to study the relationship between ESG disclosure and CFP. The results show that ROA and Tobin'Q positively correlate with ESG disclosure. Satisfactory ESG disclosure does improve financial performance. Nevertheless, in this study, Tobin'Q has no significant positive correlation with ESG disclosure, E, S, and G disclosure. There is a significant and positive correlation between ROA and them.